The need to harmonize the laws of the European Union regarding the succesion law - Laura-Dumitrana Rath-Boşca; Loredana Mirela Barmoș; Ioana Andreea Mihale (Agora International Journal of Economical Sciences (AIJES), 2016)
The inheritance implies a balance between the will of the one who plans the anticipated transmission of his assets and the ones waiting for it. The creditors are equally put into equation in the transmission of the succession. The relations between these three categories of interest are regulated differently regarding the laws of succession of the states that favor either the interests of the interested in planning his succession or trying a "equilibrium" dampening discretion of the author of the inheritance, trying to protect his close family members (reserved to)
Keywords: 330